2017
DOI: 10.18632/oncotarget.18231
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node metastasis and the physicochemical micro-environment of pancreatic ductal adenocarcinoma xenografts

Abstract: Pancreatic ductal adenocarcinoma (PDAC) patients develop lymph node metastases early and have a particularly poor prognosis. The poor prognosis has been shown to be associated with the physicochemical microenvironment of the tumor tissue, which is characterized by desmoplasia, abnormal microvasculature, extensive hypoxia, and highly elevated interstitial fluid pressure (IFP). In this study, we searched for associations between lymph node metastasis and features of the physicochemical microenvironment in an att… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 77 publications
(108 reference statements)
0
7
0
Order By: Relevance
“…Intramuscular transplantation was preferred to subcutaneous transplantation because subcutaneous HL-16 and Panc-1 tumors, in contrast to their intramuscular counterparts, develop large central necroses during growth. Moreover, it should be noticed that the histological appearance of intramuscular HL-16 and Panc-1 tumors is similar to that of cervical and pancreatic tumors in humans [25], [30].…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Intramuscular transplantation was preferred to subcutaneous transplantation because subcutaneous HL-16 and Panc-1 tumors, in contrast to their intramuscular counterparts, develop large central necroses during growth. Moreover, it should be noticed that the histological appearance of intramuscular HL-16 and Panc-1 tumors is similar to that of cervical and pancreatic tumors in humans [25], [30].…”
Section: Discussionmentioning
confidence: 81%
“…In previous studies, we have shown that the development of lymph node metastases is associated with high IFP in the primary tumor in human melanoma, cervical carcinoma, and pancreatic carcinoma xenografts [7], [9], [30], [36], [37]. In those studies, tumor IFP was measured in a single position in the tumor center assuming that IFP was uniformly elevated throughout the central tumor region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, an intramuscular site was chosen to avoid tumor movement due to respiration during the DCE-MRI. We have shown previously that intramuscular BxPC-3 and Panc-1 tumors have several microenvironmental features in common with human PDACs, including a histological appearance characterized by a dense collagen-rich extracellular matrix [38] , [45] . Furthermore, the numerical values of fraction of hypoxic tissue, microvascular density, and interstitial fluid pressure of intramuscular BxPC-3 and Panc-1 tumors are similar to those reported for orthotopic and genetically engineered mouse models of PDAC as well as human PDACs [45] .…”
Section: Discussionmentioning
confidence: 99%
“…Euthanized mice were examined for lymph node metastases in six pairs of lymph nodes ( i.e. , popliteal lymph nodes, inguinal lymph nodes, proper axillary lymph nodes, accessory axillary lymph nodes, medial iliac lymph nodes, and renal lymph nodes), as described elsewhere [ 46 ]. The presence of metastatic growth in lymph nodes was confirmed by histological examination.…”
Section: Methodsmentioning
confidence: 99%